Combination of Body Acupuncture with Scalp and Ear Microacupuncture in Treating Alzheimer's Dementia in Elderly, A Case Report - fitriani, Elies; Roosheroe, Arya Govinda; Nareswari, Irma; Viventius, Yoshua; Srilestari, Adiningsih (Journal of Agromedicine and Medical Sciences, 2024)
Dementia refers to impairment in more than one domain of cognitive function. The most common cause of dementia is Alzheimer's dementia (AD). AD is associated with the influence of amyloid, oxidative stress, as well as abnormal phosphorylation of the protein Tau which forms neurofibrillary plaques in neurons. Clinical symptoms include progressive memory impairment for current events, cognitive impairment, general confusion, agitation, delusions, social disinhibition, and paranoia. A 68 year old man complained of rapid forgetfulness and decreased cognitive function accompanied by insomnia. Acupuncture manual therapy was performed at points GB20, LI4, HT7, KI3 bilaterally and EX-HN1, EX-HN3, GV20, CV9, CV4, CV3. Combine with scalp acupuncture Zhu Scalp Head and Face, as well as bilateral anterior hypothalamus and master cerebral ear points. Electroacupuncture 2 Hz continuous wave electroacupuncture at points ST25-ST28, CV12-CV6, and ST36-SP6. Therapy is carried out 2 times a week. Evaluation using MMSE ad PSQI. After 10 treatments, there was improvement in clinical symptoms, MMSE and PSQI scores. Manual acupuncture and electroacupuncture, a combination of body points, scalp and ear microcupuncture are useful in the management of Alzheimer's dementia accompanied by insomnia as non-pharmacological adjuvant therapy with positive results. Keywords: Manual acupuncture, electroacupuncture, scalp microacupuncture, ear microacupuncture, Alzheimer's dementia